2021
DOI: 10.1016/j.csbj.2021.09.017
|View full text |Cite
|
Sign up to set email alerts
|

An Ebola, Neisseria and Trypanosoma human protein interaction census reveals a conserved human protein cluster targeted by various human pathogens

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…5 , panel a). In our recent study, we have identified that PCNA is also a preferential target of the Ebola virus [22] . ZRANK score for AFUA_1G04950-CDK4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 , panel a). In our recent study, we have identified that PCNA is also a preferential target of the Ebola virus [22] . ZRANK score for AFUA_1G04950-CDK4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EEF1A affects the prognosis of tumors such as those of the lung and stomach ( Kawamura et al, 2014 ; Li et al, 2017 ). EEF1A1 influences the host–bacterial and viral interactions through the cytoskeleton and its regulation ( Gupta et al, 2021 ). EEF1A can mediate the anti-viral activity of plitidepsin against SARS-CoV-2 and inhibit viral replication in the lungs ( White et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EEF1A affects the prognosis of tumors such as those of the lung and stomach (Kawamura et al, 2014;Li et al, 2017). EEF1A1 influences the host-bacterial and viral interactions through the cytoskeleton and its regulation (Gupta et al, 2021). EEF1A can mediate the antiviral activity of plitidepsin against SARS-CoV-2 and inhibit viral replication in the lungs (White et al, 2021).…”
Section: Classification Rules In Monocytesmentioning
confidence: 99%